Krisztina Egerszegi's Full Stroke at 65 m of Her 200 m Backstroke Gold Medal Swim at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Krisztina Egerszegi's Full Stroke at 65 m of Her 200 m Backstroke Gold Medal Swim at the Atlanta Olympic Games 1996.